2019
DOI: 10.1186/s13099-019-0334-5
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome analysis of clinical Shigella strains reveals plasmid pSS1653 with resistance determinants: a triumph of hybrid approach

Abstract: Shigella is ranked as the second leading cause of diarrheal disease worldwide. Though infection occurs in people of all ages, most of the disease burden constitutes among the children less than 5 years in low and middle income countries. Recent increasing incidence of drug resistant strains make this as a priority pathogen under the antimicrobial resistance surveillance by WHO. Despite this, only limited genomic studies on drug resistant Shigella exists. Here we report the first complete genome of clinical S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This element recently drove a prolonged S. sonnei outbreak among MSM in Victoria, Australia [17] but few CTX-M Shigella plasmids have been characterised [18]; seemingly only one other has been described in detail, in a Swiss S. sonnei isolate [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This element recently drove a prolonged S. sonnei outbreak among MSM in Victoria, Australia [17] but few CTX-M Shigella plasmids have been characterised [18]; seemingly only one other has been described in detail, in a Swiss S. sonnei isolate [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, in 2015 Public Health England (PHE) described an ESBL-producing S. sonnei MSM cluster [ 16 ] conferred by a pKSR100-like plasmid (p183660), which had acquired bla CTX-M-27 . This element recently drove a prolonged S. sonnei outbreak among MSM in Victoria, Australia [ 17 ] but few CTX-M Shigella plasmids have been characterised [ 18 ]; seemingly only one other has been described in detail, in a Swiss S. sonnei isolate [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prophage 1 and 3 matched to phiCD38-2/phiCD111/phiCD146 and phiCD6356 phages respectively, reported earlier from C. difficle ( Fortier and Moineau, 2007 ; Sekulovic et al, 2014 ). On the other hand, prophages (Geobac_E2/Bacill_phIS3501/Coryne_StAB) identical to prophage 4 are also reported in the genus Clostridium ( Smith et al, 2021 ) as well as in other species such as Shigella ( Muthuirulandi Sethuvel et al, 2019 ) and Corynebacterium (NC_048780). Phage vB_CpeS-CP51 (prophage 2), has been initially recognized as a temperate bacteriophage of C. perfringens ( Gervasi et al, 2013 ) and was later reported also in C. chauvoei ( Frey and Falquet, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the MinION reads was assessed using MinIONQC ( https://github.com/roblanf/minion_qc ). The hybrid assembly was performed using the resulting Ion Torrent reads (1,571,892) and MinION reads (1,745,808) using Unicycler (v.0.4.7) as described earlier ( 7 9 ). Unicycler utilizes SPAdes v.3.12 by default to assemble the short reads along with error correction and quality checks.…”
Section: Announcementmentioning
confidence: 99%